Pengembangan Kegiatan Ekoeduwisata Melalui Pemberdayaan Masyarakat Dan Rehabilitas Ekosistem Mangrove Di Desa Sawapudo Kabupaten Konawe - La Ode Midi; La Ode Muhammad Erif; Sitti Leomo; Asrianti Arif; Nurhayati Hadjar; Wa Ode Siti Nur Alam; Surya Cipta Ramadhan Kete; Eka Rahmatiah Tuwu (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Sawapudo Village, known for its unique coastal features including beaches, karst cliffs, and mangrove vegetation, holds tourism potential. However, a lack of wise management has led to degradation, including mangrove loss and over-exploitation of rare species. Community involvement is crucial for sustainable management. Through Integrated Thematic Community Services in July-August 2019, efforts were made to address these issues. The activities aimed to educate the community on tourism village management, improve local skills in souvenir making, and enhance digital presence through website creation and social media management. Proposed solutions included institutional strengthening, greening tourism spots, promoting IT-based tourism, producing eco-friendly souvenirs, and establishing a village website. These initiatives aim to boost the local economy and position Sawapudo as a natural tourism destination.